Cuttlefish Early Development and Behavior Under Future High CO2 Conditions - Moura, Érica; Pimentel, Marta; Santos, Catarina P.; Sampaio, Eduardo; Pegado, Maria Rita; Lopes, Vanessa Madeira; Rosa, Rui (Frontiers in Physiology, 2019)
The oceanic uptake of carbon dioxide (CO2) is increasing and changing the seawater chemistry, a phenomenon known as ocean acidification (OA). Besides the expected physiological impairments, there is an increasing evidence of detrimental OA effects on the behavioral ecology of certain marine taxa, including cephalopods. Within this context, the main goal of this study was to investigate, for the first time, the OA effects (∼1000 μatm; ΔpH = 0.4) in the development and behavioral ecology (namely shelter-seeking, hunting and response to a visual alarm cue) of the common cuttlefish (Sepia officinalis) early life stages, throughout the entire embryogenesis until 20 days after hatching. There was no evidence that OA conditions compromised the cuttlefish embryogenesis – namely development time, hatching success, survival rate and biometric data (length, weight and Fulton’s condition index) of newly hatched cuttlefish were similar between the normocapnic and hypercapnic treatments. The present findings also suggest a certain behavioral resilience of the cuttlefish hatchlings toward near-future OA conditions. Shelter-seeking, hunting and response to a visual alarm cue did not show significant differences between treatments. Thus, we argue that cuttlefishes’ nekton-benthic (and active) lifestyle, their adaptability to highly dynamic coastal and estuarine zones, and the already harsh conditions (hypoxia and hypercapnia) inside their eggs provide a degree of phenotypic plasticity that may favor the odds of the recruits in a future acidified ocean. Nonetheless, the interacting effects of multiple stressors should be further addressed, to accurately predict the resilience of this ecologically and economically important species in the oceans of tomorrow.